Ethical and Emotional Leadership as Predictors of Gen Z Employee Retention: Evidence from Indonesia’s Banking Sector - Natalie, Abigel Chintya; Tandelilin, Elsye; Darmasetiawan, Noviaty Kresna (Dinasti Publisher, 2025)
This study analyzes the influence of ethical leadership, emotional leadership, and continuous performance management on quitting intentions among Generation Z employees in the Indonesian banking sector. Using a quantitative survey approach, data were collected from Generation Z employees working in banks in Surabaya and analyzed with Structural Equation Modeling using SmartPLS3 to examine the relationships among latent variables simultaneously. The empirical results indicate that both ethical leadership and emotional leadership have a positive impact on employee motivation and performance, whereas continuous performance management does not show a significant effect. Motivation partially mediates the relationship between leadership styles and employee performance, and performance has a negative effect on quitting intentions. These findings highlight the strategic importance of ethical and emotional leadership practices, supported by continuous performance management efforts, to strengthen employee retention and improve organizational effectiveness. The study offers novelty by integrating two leadership styles and a sustainable performance management system into a single empirical model tested in the context of Generation Z employees in the Indonesian banking industry, a setting that has received limited prior scholarly attention.